Pie Paradise Evolving Social Contract and Personal Commitment Produces Start-up Success in a Harsh Masculine Entrepreneurship Ecosystem - Khan RAHATULLAH Muhammad (Communications of International Proceedings, 2020)
Saudi Arabia scores 36 in ‘long term orientation’ dimension in Hofstede’s studies. People in such societies exhibit great respect for traditions. Similarly, Saudi Arabia is labelled as a collectivistic society where the hierarchies are recognized and followed. This is even true in families as the males dominate. Saudi Arabia therefore, is seen as an ultra-conservative society where the rights of women are often limited and they need male permission to perform any and every work or even study and travel. The driving ban on women has only recently been lifted. The society has started to evolve and the women are now asserting their skills and acumen. The traditions still remain very tightly followed. The national entrepreneurship ecosystem is also considered harsh as women participation is negligible. However, there are signs of cracks appearing in the old-fashioned tradition clad society. The women have been successful as start-ups. Having a faceoff with conventional elements is exceptional as this case narrates. It brings to light the changing nature and the role of society, family and determination of the start-up to face challenges and succeed. The case identifies the challenges, punitive and strict systems and social laws. It identifies evolution occurring in social contract where there seems an implicit agreement among the society to accept women in business fields among others. Case helps the reader understand the prowess of young female start-ups; how some of these young females are breaking fetters and taboos attached are blown. The role of personality characteristics and assertiveness are important in changing scenario.
Keywords: Female entrepreneurs; Saudi Arabia; Harsh entrepreneurial ecosystem; Leadership